Encyonema bonapartei sp. nov.: a new freshwater diatom species (Cymbellales, Bacillariophyceae) in canals of Great East region (France) - Heudre, David; Wetzel, Carlos E.; Ector, Luc (Phytotaxa, 2016)
As a part of the Monitoring Program of the European Water Framework Directive, the phytobenthos of streams and canals was studied in the Great East region of northeastern France (French part of Rhine-Meuse river basin and Seine-Normandy basin). A new species, Encyonema bonapartei was identified in canals. Its morphology was examined in detail using light and scanning electron microscopy, which showed a unique combination of measurements and shape: valves are clearly asymmetrical and semi-elliptical to semi-elliptical-lanceolate with central area extended on ventral margin by shorter or missing striae. The striation is almost parallel with areolae indistinguishable in the light microscope. This paper provides comparison with morphologically similar species: Cymbopleura hustedtii, Encyonema brehmii, E. kalbei, E. marvanii, E. reichardtii and E. yuwadeeanum. Encyonema bonapartei was first discovered in the East Canal in 2014. It was then found in the Rhône-to-Rhine Canal and Champagne and Burgundy Canal in 2015. Most likely it will spread further in connected waterways. Information on its autecology is presented using the physicochemical data of the type locality.